Northern Europe and the Future of the EU : Nordeuropa und die Zukunft der EU. - Hoibraaten, Helge (Nordeuropäische Studien - Band 23., 2012)
& B & Hauptbeschreibung & /b & & br/ & The current relationship between the Nordic countries and the European Union appears complex and confusing. Although Denmark, in 1973, and Sweden and Finland, in 1995, joined the European Union, the entry of Norway into the Union was rejected in the plebiscites of 1972 and 1994. Furthermore, Nordic EU members enjoy permanent exceptions to their integration into the EU: Denmark and Sweden, like the U.K., have declined to become part of the monetary union. Finland is essentially the only Nordic country that entered the EU without substantial exceptions. A membership.